Ifo World Economic Survey December 2002 - Gernot Nerb; Anna Stangl (Ifo World Economic Survey, 2002)
World Economic Climate worsened in October - Economic expectations deteriorated but remained positive - Inflation in 2002 expected to slow down - Short-term interest rates are expected to sink in coming months / Long-term rates will stabilize at the current low level - The major world currencies are close to an equilibrium situation - Ways to raise standards of corporate governance
Keywords: 330